2002
DOI: 10.1186/1471-2407-2-29
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiling of twenty promoter-CpG islands of genes which may contribute to hepatocellular carcinogenesis

Abstract: Background: Hepatocellular carcinoma (HCC) presents one of the major health threats in China today. A better understanding of the molecular genetics underlying malignant transformation of hepatocytes is critical to success in the battle against this disease. The methylation state of C5 of the cytosine in the CpG di-nucleotide that is enriched within or near the promoter region of over 50 % of the polymerase II genes has a drastic effect on transcription of these genes. Changes in the methylation profile of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
163
5
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(175 citation statements)
references
References 25 publications
6
163
5
1
Order By: Relevance
“…Allelic loss of RASSF1A locus could be detected in microdissected tissues from low-and high-grade dysplastic nasopharyngeal epithelial lesions (Lo and Huang, 2002;Chow et al, 2004). RASSF1A is also commonly inactivated in other human cancers including gastric cancer (Kang et al, 2002), hepatocellular carcinoma (Yu et al, 2002) and small-cell lung cancer (Dammann et al, 2001); suggesting its common involvement in human carcinogenesis. Reconstitution of RASSF1A expression in a NPC cell line, C666-1, induced loss of viability, growth suppression, diminished invasiveness and anchorage-independence growth properties (Chow et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Allelic loss of RASSF1A locus could be detected in microdissected tissues from low-and high-grade dysplastic nasopharyngeal epithelial lesions (Lo and Huang, 2002;Chow et al, 2004). RASSF1A is also commonly inactivated in other human cancers including gastric cancer (Kang et al, 2002), hepatocellular carcinoma (Yu et al, 2002) and small-cell lung cancer (Dammann et al, 2001); suggesting its common involvement in human carcinogenesis. Reconstitution of RASSF1A expression in a NPC cell line, C666-1, induced loss of viability, growth suppression, diminished invasiveness and anchorage-independence growth properties (Chow et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…5,6 Several genes located on chromosome 3p have been studied in HCC as well as CC and include RASSF1A on 3p21.31, FHIT at 3p14.2, RIZ1, VHL at 3p25. [7][8][9][10] These results directed an intensive search for possible tumor suppressor genes located in the 3p21 region for one or more genes that could function as gatekeepers in molecular pathogenesis of human cancers. A group of candidate tumor suppressor genes (designated BLU, SEMAPHORIN 3B, or RASSF1A) has recently been mapped to this critical gene-rich region.…”
mentioning
confidence: 99%
“…In the past decade, researches on hepatocellular carcinoma (HCC) related genes have successfully demonstrated that the expression of sets of genes are significantly down-regulated or silenced by the abnormal methylation of CpG islands in gene promoters in early HCCs. Multiple data from these studies in liver tissue demonstrate that except for the process from hepatic cirrhosis (HC) to HCC, there is an obvious change in the methylation rate during the process from normal to HC (Yu et al 2002;Li et al 2004;Nishida et al 2012). For example, in a qualitative investigation using methylation-specific PCR (MSP) to detect various gene methylation status, the hypermethylation rate of promoter was found to be 15% in liver cirrhosis tissue and 0% in normal liver tissue (Zhang et al 2008).…”
mentioning
confidence: 99%
“…CpG islands are CpG dinucleotide-rich areas located mainly in the gene promoter regions. DNA methylation can add methyl groups to CpG island, decrease gene transcription activity and may account for gene inactivation in the pathogenesis process (Yu et al 2002). Among various kinds of epigenetic modifications, many studies have focused on DNA methylation.…”
mentioning
confidence: 99%